2005
DOI: 10.1097/01.mbc.0000178827.52242.89
|View full text |Cite
|
Sign up to set email alerts
|

Clotting time analysis of citrated blood samples is strongly affected by the tube used for blood sampling

Abstract: Our aim was to establish whether differences in clotting times for recalcified blood and plasma samples might be explained by the use of different blood collection tubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 16 publications
4
21
0
Order By: Relevance
“…Although these studies attempted to eliminate the contribution of the contact system to FXI activation by adding CTI or a FXII antibody to the isolated plasma, these additions did not eliminate the FXIa that was already formed via contact system activation during the blood draw and plasma isolation (ref. 28 and Fig. 2 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies attempted to eliminate the contribution of the contact system to FXI activation by adding CTI or a FXII antibody to the isolated plasma, these additions did not eliminate the FXIa that was already formed via contact system activation during the blood draw and plasma isolation (ref. 28 and Fig. 2 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are plenty of clinical papers about microparticle detection, only few publications deal with the critical factors affecting processing and quantification of microparticles whether directly obtained from patients' plasma samples or generated in vitro. Issues that have been investigated include influences of blood sampling site and technique [3], needle bore size [4], anticoagulant in collection tube [5], storage time at room temperature, type of quantification beads [6] and instrument settings of flow cytometer [7]. Furthermore, it could also be shown that different agents used for stimulation affect size, antigen and phosphatidylserine exposure of microparticles [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…21 Although the exact mechanisms of FXIIa generation in the Amelung assay were not identified, it is, in this context, worth reiterating the well-known fact that in every conventional in vitro assay used to monitor coagulation, small, but not negligible, amounts of FXII will eventually be generated by plastic or metal surfaces in contact with plasma. [22][23][24][25] In the absence of strong activators of coagulation, such artifactual sources of FXIIa will become the predominant procoagulant mechanism. Thus, the identity of the "foreign surface" triggering generation of FXIIa, as referred to in the above quote, is far more likely to have been the moving metal ball used to monitor coagulation in the Amelung instrument than platelet-derived polyphosphates.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] In the absence of strong activators of coagulation, such artifactual sources of FXIIa will become the predominant procoagulant mechanism. Thus, the identity of the "foreign surface" triggering generation of FXIIa, as referred to in the above quote, is far more likely to have been the moving metal ball used to monitor coagulation in the Amelung instrument than platelet-derived polyphosphates.…”
mentioning
confidence: 99%